Resultatbaseret statsstyring af lokal kernevelfærd - Østergaard Møller, Marie; Normann Andersen, Vibeke (Politik, 2017)
Results based management is an example of a management approach affecting policy implementation through specific policy tools. It is legitimized as a way to strengthen control with public expenses and to produce more effective welfare services. The article is based on a systematic literature review of results based state management of local welfare in three policy areas (primary school, employment and social service) and focuses on what happens when results based management is implemented in welfare organizations. The results from the review point to a range of non-intended consequences and the argument put forward is that they are related to a discrepancy between performance goals and welfare professional work. Besides theory on unintended consequences of results based-management, the article draws on frontline theory and sociology of professions. More specific, we use a concept of classification to explain what happens when results based management meets welfare professionals with a large room of discretion.